A genomic atlas of mouse hypothalamic development (2010)
ABSTRACT: The hypothalamus is a central regulator of many behaviors that are essential for survival, such as temperature regulation, food intake and circadian rhythms. However, the molecular pathways that mediate hypothalamic development are largely unknown. To identify genes expressed in developing mouse hypothalamus, we performed microarray analysis at 12 different developmental time points. We then conducted developmental in situ hybridization for 1,045 genes that were dynamically expressed over the course of hypothalamic neurogenesis. We identified markers that stably labeled each major hypothalamic nucleus over the entire course of neurogenesis and constructed a detailed molecular atlas of the developing hypothalamus. As a proof of concept of the utility of these data, we used these markers to analyze the phenotype of mice in which Sonic Hedgehog (Shh) was selectively deleted from hypothalamic neuroepithelium and found that Shh is essential for anterior hypothalamic patterning. Our results serve as a resource for functional investigations of hypothalamic development, connectivity, physiology and dysfunction.